Urban Revitalization of Spatial Memory: Towards the Restoration of Identity in Contemporary Cities (Journal of Engineering, 2026)
The urban fabric of contemporary cities is experiencing a decline in spatial memory and collective identity as a result of rapid transformations in urban form and behavior. This research is based on the hypothesis that the continuity and spatial integration of the morphological structure enhance spatial perception and belonging, and that this interconnectedness forms the basis for reviving urban identity. The study adopts an analytical-comparative approach that combines digital spatial analysis using DepthmapX and social analysis through a field survey of residents. This approach compares three historic cities that represent different patterns of spatial memory revival: Fez, which preserved the coherence of its organic fabric and historical continuity; Sarajevo, which rebuilt its collective symbols through the restoration of monuments and public squares; and Aleppo, which demonstrated limited continuity in morphological structure but a strong presence of symbolic and functional memory. The hypothesis was tested by analyzing the relationship between spatial integration indicators and the axes of perception and belonging in the questionnaire, confirming the interconnectedness between urban form and social practice as a mechanism for reviving spatial memory. The study proposes a participatory design framework that integrates digital tools with community data to enhance the continuity of urban memory and identity in contemporary historic cities, emphasizing that reviving spatial memory is a fundamental approach to sustainable urban development and future conservation policies.